Acceleration methods for the convergence of vector sequences applied to multi‐physics problems. Issue 1 (December 2014) - Erbts, Patrick; Düster, Alexander
Abstract Partitioned solution approaches are well‐known strategies to solve coupled problems and have demonstrated their applicability in a wide range of multi‐physical simulations. Applying a partitioned approach opens up numerous possibilities, such as connecting different solvers or combining non‐matching meshes and time‐step sizes. On the other hand such a procedure has the drawback of only conditional stability, leading to poor convergence rates or ‐ as a worst case scenario ‐ to divergent behavior. In this contribution, we will give an interpretation of the iterative coupling process as a sequence of vectors converging to an unknown limit, which indeed represents a solution to the coupled problem. In order to improve computational efficiency, there are several practicable methods to accelerate the convergence of vector sequences. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)